2019
DOI: 10.5553/ijrj/258908912019002002003
|View full text |Cite
|
Sign up to set email alerts
|

Looking beneath the iceberg: can shame and pride be handled restoratively in cases of workplace bullying

Abstract: Central to restorative justice interventions that follow revised reintegrative shaming theory (Ahmed et al. 2001) is individual capacity to manage shame and pride in safe and supportive spaces. From a random sample of 1,967 Australians who responded to a national crime survey, 1045 completed a module about bullying experiences at work over the past year, along with the MOSS-SASD and MOPS shame and pride management scales. Those who identified themselves as having bullied others were pride-focused, not shame-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Since 2001, studies in Bangladesh and Australia have shown narcissistic pride and unacknowledged shame are consistently linked with more bullying; humble pride and acknowledged shame with less bullying (Ahmed & Braithwaite, 2011;Braithwaite & Ahmed, 2019;Braithwaite, Ahmed & Braithwaite, 2008). Narcissistic pride and unacknowledged shame are more likely to be found in workplaces where norms of respect for others have been weakened.…”
Section: The 2001 Revision Of Reintegrative Shaming Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2001, studies in Bangladesh and Australia have shown narcissistic pride and unacknowledged shame are consistently linked with more bullying; humble pride and acknowledged shame with less bullying (Ahmed & Braithwaite, 2011;Braithwaite & Ahmed, 2019;Braithwaite, Ahmed & Braithwaite, 2008). Narcissistic pride and unacknowledged shame are more likely to be found in workplaces where norms of respect for others have been weakened.…”
Section: The 2001 Revision Of Reintegrative Shaming Theorymentioning
confidence: 99%
“…Shaming and disapproval, however packaged, will be highly threatening because without humble pride, no one is there to soothe a bruised ethical identity. Regulatory practices of reintegrative shaming have the challenging task of breaking through the shield of pride that fills the holder with a sense of superiority and blamelessness (Braithwaite & Ahmed, 2019).…”
Section: The 2001 Revision Of Reintegrative Shaming Theorymentioning
confidence: 99%